Electrospray mass spectrometric investigation of the reactivity of the sulfide centers in [Pt2(μ-S)2(PPh3) 4] towards organic dihalides and the catalytic potential of this complex in the syntheses of organosulfur materials - Chong, S.H. (2014)
10.1016/S1381-1169(03)00308-X